Assessment Of Nursing Staff information And Practices About Cardiopulmonary Resuscitation (CPR) (Journal of Hama University, 2021)
Introduction: CPR is a life-saving intervention. It mainly aims to deliver oxygen and blood to vital tissues, and the CPR skills of the nursing staff must be improved so that this is reflected in reducing the mortality rate and the ability to respond quickly and effectively in the event of cardiac arrest. Aim of the study: This research aims to evaluate the information and practices of the nursing staff about CPR. Research materials and methods: A descriptive cross-sectional study was conducted using a convenience sample of 150 nurses from the intensive care and ambulance units in Tishreen University Hospital in Lattakia Governorate. The data was collected through a questionnaire form developed by the researcher. Results: The findings showed that there is a weakness in the information and practices of the nursing staff about CPR, as 46% of the studied sample had poor level of information, 30.7% were good level, 23.3% were average level, and 80% of the studied sample had poor level and 20% had moderate level of practice. Recommendations: The study recommends the necessity of conducting training courses on CPR based on the updates of American the Heart Association, and conducting research on the impact of training programs on the information and practices of nursing staff about CPR, and focusing on the importance of learning basic and advanced CPR for the nursing staff